2020
DOI: 10.1016/j.btre.2020.e00503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, proportion and organic loading rate on the performance of anaerobic digestion of food waste

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 51 publications
(59 reference statements)
2
8
0
3
Order By: Relevance
“…The results showed that the fitted Rmax values of the three models were lower than the experimental Rmax values except for the CD + WR group. Lower fitted Rmax values than the experimental Rmax values were also reported in previous anaerobic co-digestion studies [12,30]. The average Rmax values fitted by the modified logistic and Richards models were closer the experimental Rmax values than those fitted by the modified Gompertz model.…”
Section: Discussionsupporting
confidence: 77%
“…The results showed that the fitted Rmax values of the three models were lower than the experimental Rmax values except for the CD + WR group. Lower fitted Rmax values than the experimental Rmax values were also reported in previous anaerobic co-digestion studies [12,30]. The average Rmax values fitted by the modified logistic and Richards models were closer the experimental Rmax values than those fitted by the modified Gompertz model.…”
Section: Discussionsupporting
confidence: 77%
“…A study conducted with prepared and leftover food as feedstock has concluded in a specific methane yield of 869.00 mL of CH4.g /TVS [35]. Similarly, another study [33,36] has signalled the biomethane potential and specific methane yields of 725.00 and 683.00 The lab-scale batch experiments lasted for 57 days.…”
Section: Effect Of S:i Ratios On Biogas Yieldsmentioning
confidence: 98%
“…Entretanto, cabe lembrar que o valor de BMP é dependente das condições do processo (tipo de processo contínuo ou batelada, digestão úmida ou seca, temperatura e atividade do inóculo) e dos tipos e das propriedades dos resíduos (CAMPUZANO; GONZALEZ-MARTINEZ, 2016;BLASIUS et al, 2020), que dificultam a comparação entre os trabalhos.…”
Section: Testes De Bmpunclassified
“…Os desafios englobam a baixa taxa de aplicação de sólidos nos reatores, que implica na necessidade de grandes instalações, a vulnerabilidade da atividade metanogênica frente a elevadas cargas orgânicas, a variação e sazonalidade dos substratos, o longo tempo requerido para estabilização da matéria orgânica, as características do material digerido, além de desafios técnicos e tecnológicos e a quantidade e qualidade de inóculo (LI et al, 2011;KHALID et al, 2011;JEND et al, 2015;SILVEIRA et al, 2015;PARITOSH et al, 2017;POSMANIK et al, 2017;BLASIUS, 2020).…”
Section: Introductionunclassified